2022
DOI: 10.1051/0004-6361/202141501
|View full text |Cite
|
Sign up to set email alerts
|

Studying the merging cluster Abell 3266 with eROSITA

Abstract: Abell 3266 is one of the X-ray brightest galaxy clusters in the sky and is a well-known merging system. Using the ability of the eROSITA telescope onboard SRG (Spectrum Röntgen Gamma) to observe a wide field with a single pointing, we analysed a new observation of the cluster out to a radius of R200. The X-ray images highlight sub-structures present in the cluster, including the north-east-south-west merger seen in previous ASCA, Chandra, and XMM-Newton data, a merging group towards the north-west, and filamen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 64 publications
6
9
0
Order By: Relevance
“…However, this difference is small, namely of 10-15% in the full 0.7−7 keV band for low-temperature clusters (<4 keV) to which we are sensitive in the eFEDS observations. Our preliminary calibration studies with eROSITA showed that, in general, eROSITA temperatures are in good agreement with Chandra and XMM-Newton temperatures (Sanders et al 2022;Veronica et al 2022;Iljenkarevic et al 2022;Whelan et al 2021). Turner et al (2021) recently cross-matched the eFEDS cluster catalog (Liu et al 2022a) with the XMM-Newton Cluster Survey (XCS, Romer et al 2001) sample and found luminosities of 29 cross-matched clusters to be in excellent agreement.…”
Section: Resultssupporting
confidence: 62%
“…However, this difference is small, namely of 10-15% in the full 0.7−7 keV band for low-temperature clusters (<4 keV) to which we are sensitive in the eFEDS observations. Our preliminary calibration studies with eROSITA showed that, in general, eROSITA temperatures are in good agreement with Chandra and XMM-Newton temperatures (Sanders et al 2022;Veronica et al 2022;Iljenkarevic et al 2022;Whelan et al 2021). Turner et al (2021) recently cross-matched the eFEDS cluster catalog (Liu et al 2022a) with the XMM-Newton Cluster Survey (XCS, Romer et al 2001) sample and found luminosities of 29 cross-matched clusters to be in excellent agreement.…”
Section: Resultssupporting
confidence: 62%
“…Furthermore, if an emission bridge does connect the two clusters, the eRASS image will provide its observation. More generally, given the early eROSITA results on cluster outskirts and infall regions (e.g., Reiprich et al 2021;Ghirardini et al 2021;Churazov et al 2021;Veronica et al 2022;Whelan et al 2021;Sanders et al 2022), and given the close correspondence to similar structures observed in cosmological hydrodynamical simulations (e.g., Biffi et al 2022), we may expect that bridges and clumpy filaments will be discovered in several more nearby systems in the future in the eRASS. These systems can then be studied in detail after the eight surveys are completed using the SRG/eROSITA scanning mode, with which areas of tens of square degrees can be scanned efficiently, homogeneously, and deeply.…”
Section: Discussionmentioning
confidence: 73%
“…Abell 3266 has been extensively observed at X-ray wavelengths (Markevitch et al 1998;Mohr et al 1999;De Grandi & Molendi 1999;Henriksen et al 2000;Sauvageot et al 2005;Finoguenov et al 2006;Sanders et al 2022). All observational results show that Abell 3266 is undergoing a complex merger event, presenting an elongated and asymmetric X-ray surface brightness distribution, as well as an asymmetric temperature profile.…”
Section: Abell 3266mentioning
confidence: 93%